Human Capital Reputation as an Antecedent of Foreign Direct Investment Market Entry in Zimbabwe - Tafadzwa Matiza; Sandra Perks (Journal of Economics and Behavioral Studies, 2017)
This paper examines the influence that the reputation of Zimbabwe’s human capital has as an antecedent of FDI market entry opportunities in the country. By synthesizing nation branding, behavioural finance and foreign direct investment theory, this paper contributes to the growing body of knowledge in human capital as a determinant influencing foreign investor behaviour within an African economic context. Empirical data was generated from a self-administered online survey of a purposively sampled population of 305 foreign investors within the Zimbabwean context. Exploratory factor analysis extracted the items that constituted the Zimbabwean human capital construct, with Cronbach’s alpha coefficients being utilized to measure the reliability of the measuring instrument. Descriptive statistics, Pearson product-moment coefficients and multiple regression analysis were employed to further analyze the data. The results revealed that foreign investors considered the availability of a sustainable, highly productive, skilled, retainable and inexpensive workforce, as the influential human capital attributes they considered for FDI to Zimbabwe. The empirical evidence further affirmed that the reputation of Zimbabwe’s human capital is an antecedent for resource- and efficiency-seeking FDI typologies to Zimbabwe. As a result, practical guidelines are provided for the Government of Zimbabwe and the Zimbabwe Investment Authority on the potential development and promotion of Zimbabwe’s human capital for the purpose of positively influencing investor behaviour, thereby attracting FDI to the country.